Pemberdayaan Tim “Jumantik” (Juru Pemantau Jentik) di SD 14 dan 15 Koto Lalang pada Masa Pandemi - Masrizal Masrizal; Muhammad Alfarezi; Ade Betasril; Trif Vando Rahmalber (Warta Pengabdian Andalas, 2022)
Schools, apart from functioning as places of learning, can also be a threat of disease transmission if they are not appropriately managed. School age for children is also a period prone to various diseases, such as diarrhoea, infectious diseases, dengue fever, etc. In response to this problem, the formation and empowerment of the "Jumantik" Team at SDN 14 and 15 Koto Lalang. Based on realising a healthy school, this activity was carried out by forming and empowering a team of monitors for larvae, called Jumantik, in schools. Methods used were conducting a pretest and posttest, counselling, outreach to school members, and evaluation. Based on the author's observation, SDN 14 and 15 Koto Lalang has an open water canal in front of it. There was an increase in the proportion of students' knowledge level after being given counselling compared to before counselling. It is hoped that SDN 14 and SDN 15 Koto Lalang will further improve behaviour related to DHF, CTPS habits, and the implementation of health protocols during the Covid - 19 pandemic. It is hoped that school residents at SDN 14 and SDN 15 Koto Lalang can use the hand washing facilities, especially in face-to-face learning programs during the Covid-19 pandemic.